Factors Affecting Mobility after Knee Arthroplasty - Hiyama, Yoshinori; Wada, Osamu; Nakakita, Satoshi; Mizuno, Kiyonori (The Journal of Knee Surgery, 2017)
Restricted mobility is a major issue for individuals with knee osteoarthritis (OA). Total knee arthroplasty (TKA) is expected to improve mobility in people with knee OA by alleviating pain and improving walking ability. The present study aimed to describe the time course of mobility after TKA and to identify the factors affecting mobility after TKA. This prospective cohort study comprised 62 patients undergoing TKA, evaluated at 1 month preoperatively, as well as at 1, 3, and 6 months postoperatively. Outcome measures included mobility (Life Space Assessment; LSA), self-efficacy for walking tasks (modified Gait Efficacy Scale; mGES), and physical (quadriceps strength and the Timed Up and Go; TUG test) and knee function (the Knee Society Score questionnaire). As a result, a total of 59 patients (mean age: 71.7 years; range: 58–79 years) had completed all postoperative assessments. Compared with preoperative values, patients showed decreased LSA and mGES scores at 1 month postoperatively. We found improvements in those scores from the 1-month to the 3- and 6-month assessment; however, there was no difference in the LSA and mGES scores between the preoperative and 6-month assessment. We also found improvements in quadriceps strength, the TUG score, the Knee Society Score, and pain scores from the preoperative to the 6-month assessment. Additionally, at 6 months postoperatively, the mGES and TUG scores significantly affected mobility. Our results suggest that mobility at 6 months after TKA is similar to preoperative level and self-efficacy for walking tasks and functional ability are important factors in improving mobility after TKA.
Keywords: knee arthroplasty; mobility; self-efficacy